Tall-cell variant of papillary thyroid carcinoma: literature review and case reports - E. V. Borodavina; P. A. Isaev; F. S. Sevrukov; A. V. Sidorin; V. V. Polkin; A. A. Ilyin; N. V. Severskaya; T. A. Agababyan; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи)
The tall-cell variant of papillary thyroid carcinoma is a rare malignancy characterized by an aggressive course, low relapse-free survival, early metastasis, and frequent development of radioiodine refractoriness. We report two cases of tall-cell papillary thyroid carcinoma in patients who had disease progression after combination treatment and started to receive lenvatinib. We observed partial and complete regression of metastases in response to lenvatinib. Our findings are consistent with the results of other studies assessing treatment efficacy for disseminated tall-cell papillary thyroid carcinoma.